Sexual Transmission of HCV in Heterologous Monogamous Spouses. (24th November 2014) - Rafik, Mona M.; El Shazly, Yehia; Abbas, Amal A.; Abd Elhady, Walid; Ragab, Dina; AlShennawy, Dina
Abstract : We screened for evidence of HCV infection in healthy heterologous monogamous spouses of chronic HCV patients and studied the relation with various risk factors. A cross-sectional study of fifty healthy monogamous heterosexual spouses of HCV-positive index cases was carried out. All participants were HBV and HIV negative. The association with various risk factors was studied. Five spouses (10%) showed evidence of HCV infection. Two partners were positive for HCV antibody alone (4%) and 3 for antibody and HCV PCR (6%). No association was found between HCV infection and various sociodemographic parameters with the exception of older age categories. Intraspousal transmission of HCV may be an important source of spread of HCV infection. The reservoir of HCV-infected individuals in Egypt is sizable, and sexual transmission of HCV may contribute to the total burden of infection in Egypt.